Analisa Konsentrasi Reaktan Terhadap Produk Gas Hidrogen Pada Reaksi Hidrolisis Kompor Berbahan Bakar Limbah Kaleng Bekas - Sukadi; Novarini (Jurnal INOVATOR, 2021)
Inorganic waste is rubbish that cannot be broken down by nature such as metals, plastics and glass. Garbage for the city of Jambi is a problem that has not been resolved to date. One example of the type of metal waste that can be managed is Aluminum such as used beverage cans. One way that technology can be developed to treat aluminum waste packaging for used beverage cans (soft drinks) is by way of recycling. The method that can be used is the hydrolysis process to produce hydrogen gas as stove fuel. The hydrolysis process is carried out by mixing Sodium Hydroxide, Aluminum, and Water. An analysis of the composition of Aluminum, Water and Sodium Hydroxide (NaOH) is carried out to produce maximum hydrogen gas with a fixed reactor volume. the results of research conducted obtained the volume of H volume gas formed, the highest pressure and temperature (130 l, 200 psi and 100 ° C) with the use of maximum reactants, namely aluminum from 400 g canned waste and 4N NaOH. NaOH acts as a catalyst in the aluminum reaction and water forms NaAl (OH) ₄ which releases hydrogen gas in the exothermic reaction..